Diaporthe atlantica enhances tomato drought tolerance by improving photosynthesis, nutrient uptake and enzymatic antioxidant response - Pereira, Eric C.; Zabalgogeazcoa, Iñigo; Arellano, Juan B.; Ugalde, Unai; Vázquez de Aldana, Beatriz R. (Frontiers in Plant Science, 2023)
Functional symbiosis with fungal endophytes can help plants adapt to environmental stress. Diaporthe atlantica is one of the most abundant fungal taxa associated with roots of Festuca rubra subsp. pruinosa, a grass growing in sea cliffs. This study aimed to investigate the ability of a strain of this fungus to ameliorate the impact of drought stress on tomato plants. In a greenhouse experiment, tomato plants were inoculated with Diaporthe atlantica strain EB4 and exposed to two alternative water regimes: well-watered and drought stress. Several physiological and biochemical plant parameters were evaluated. Inoculation with Diaporthe promoted plant growth in both water treatments. A significant interactive effect of Diaporthe-inoculation and water-regime showed that symbiotic plants had higher photosynthetic capacity, water-use efficiency, nutrient uptake (N, P, K, Fe and Zn), and proline content under drought stress, but not under well-watered conditions. In addition, Diaporthe improved the enzymatic antioxidant response of plants under drought, through an induced mechanism, in which catalase activity was modulated and conferred protection against reactive oxygen species generation during stress. The results support that Diaporthe atlantica plays a positive role in the modulation of tomato plant responses to drought stress by combining various processes such as improving photosynthetic capacity, nutrient uptake, enzymatic antioxidant response and osmo-protectant accumulation. Thus, drought stress in tomato can be enhanced with symbiotic fungi.